FRANCHISE MODEL OF BUSINESS IN FOODSERVICE INDUSTRY - Patrusheva A.V. (Техника и технология пищевых производств)
The article is devoted to analysis of the franchise market in foodservice industry in the context of franchise coffee houses. The aim of the article is the analysis of the franchise business model in foodservice business. The article analyzes the current state of the market franchise coffee houses, the state of demand for the services of such establishments and tendencies to changes, changes in the market of coffee houses in connection with the economic crisis, peculiarities of franchising networks operating at present in the market and offering a franchise for purchasing. The features of different types of coffee houses operating in the Russian market as belonging to the network structures and independent ones are analyzed. It is shown that the structure of the network can develop both by organizing one’s own establishment and by selling the franchise. Marked are the advantages of the franchisor he gets when transforming his business into a franchise network as well as the advantages of the franchisee he gets when purchasing a franchise. The data on the franchise of some coffee houses offered for sale currently are considered. The conclusions on the state of the market of coffee houses, the reasons for its growth and profitability and feasibility for organizing of new establishments, the reasons for popularity of some establishments in the Russian market are given. The conclusion about the viability of franchising networks operating in the market at present, their advantages and disadvantages has been done. The effect of the conversion of independent businesses into the franchise network structure on the value of business owners’ potential economic gains and the capital of the company has been pointed out.